Decomposition of Riemannian Recurrent Curvature Tensor Manifolds of First Order - Negi, U. S.; Chauhan, Preeti; Sulochana (Journal of Nepal Mathematical Society, 2022)
Takano [6] premeditated decomposition of curvature tensor in a recurrent Riemannian space. After that, Negi and Bisht [3] defined and deliberated decomposition of recurrent curvature tensor fields in a Kaehlerian manifolds of first order. We have calculated the decomposition of Riemannian recurrent curvature tensor manifolds of first order and some theorems established using the decomposition tensor field.